Anthelmintics efficacy against intestinal strongyles in horses of Sardinia, Italy. Issue 2 (June 2016) - Sanna, G.; Pipia, A.P.; Tamponi, C.; Manca, R.; Varcasia, A.; Traversa, D.; Scala, A.
Abstract: Intestinal strongyles (IS) are the most important parasites of equids, due to their high prevalence worldwide, pathogenicity and the spread of drug-resistant populations. Despite the large number of horses bred in Sardinia Island, Italy, no data are available on the efficacy of anthelmintic compounds in the control of horse strongylosis. Therefore the aim of the present study was to evaluate the efficacy of five commercial anthelmintic formulations containing fenbendazole (FBZ), pyrantel (PYR), moxidectin (MOX) and two ivermectin formulations (IVM1 and IVM2) against IS in Sardinia by performing a fecal egg count reduction test (FECRT) and investigating the egg reappearance period (ERP) after treatment. In total, 74 horses from 7 farms were examined. Coprocultures performed for individual fecal samples collected at the day of the treatment revealed that cyathostomins were the predominant parasitic species (98.6%). The FECR for all horses belonging to the treatment groups after two weeks was ≥ 95% with a 95% C.I. > 90%. The expected ERP did not decrease in any of the treatment group as FECR values < 90% were found at D60 for FBZ, at D90 for PYR and IVM1, at D150 for IVM2. All horses treated with MOX showed FECRT > 90% for the entire duration of the trial until D150. The results of the present survey indicate that drug-resistant cyathostomin populations are not present in the examined horse population, contrariwise to what observed in other Italian and European regions. The reasons and implications of these results are discussed.